The treatment of acute Rockwood type III acromio-clavicular joint dislocations by two different surgical techniques - Biz, Carlo; Berizzi, Antonio; Cappellari, Alessandro; Crimì, Alberto; Tamburin, Stefano; Iacobellis, Claudio (Acta Biomedica Atenei Parmensis, 2015)
Background and aim of the work: the treatment of acute type III acromio-clavicular Rockwood dislocations is still a matter of discussion in orthopaedic surgery. The purpose of this study, retrospective and comparative, is to evaluate the long-term results of two different surgical techniques of temporary stabilization using K-wires with and without tension band wiring. Methods: one hundred patients, treated from January 2007 and November 2010, were subdivided into two groups according to the surgical method used. They were clinically and radiographically assessed, and the results were compared with those present in the literature. Results: the patients were clinically and radiologically evaluated with a mean follow-up of 44.7 months (range 25-60 months). According to the Constant Score, the positive results were 87.4% in group A and 90.2% in group B, without significant statistical difference (p>0.05). However, there were numerous complications, especially metal-work mobilization. Conclusions: the results that we have obtained, in part disappointing on the short-term, but positive overall and in line with the literature at long-term follow-up, do not clarify which of the two techniques is superior.